Integrated Stress Field Estimation and Implications for Enhanced Geothermal System Development in Acoculco, Mexico. (January 2021) - Kruszewski, Michal; Hofmann, Hannes; Alvarez, Fidel Gomez; Bianco, Caterina; Haro, Adrian Jimenez; Garduño, Victor Hugo; Liotta, Domenico; Trumpy, Eugenio; Brogi, Andrea; Wheeler, Walter; Bastesen, Eivind; Parisio, Francesco; et al.
Highlights: The in-situ stress regime of the Acoculco field can be described as transtensional Pore pressure and Sv gradients equal to 8.73 and 24.3 ± 1.5 MPa·km -1 respectively Shmin and SHmax gradients equal to 22.8 ± 3.3 and 42.9 ± 28.5 MPa·km -1 respectively Maximum pressure required to enhance the rock permeability is estimated Potential EGS development options for the Acoculco field are discussed Abstract: Data gathered from two geothermal exploration wells in the Acoculco caldera, within the Trans-Mexican Volcanic Belt, indicated that temperature is high enough for economic utilization, but permeability is insufficient. Hence, heat exploitation at this location may only be possible by Enhanced Geothermal System (EGS) technologies. To evaluate the potential for EGS development, a wide range of exploration work has been carried out in the framework of the international research project GEMex. In this manuscript, we present best estimates of the in-situ stress field conditions at the site – an important, yet highly uncertain, parameter for stimulation planning. The study is based on geological data, drilling parameters, geophysical logging, laboratory measurements on collected rock samples, and statistical analyses. The in-situ stress regime of the Acoculco geothermal area can be described as transtensional with a maximum horizontal stress striking in the NE-SW direction, a pore pressure gradient of 8.73 MPa·km -1, a minimum horizontal stress gradient of 22.8 ± 3.3 MPa·km -1, a vertical stress gradient of 24.3 ± 1.5 MPa·km -1, and a maximum horizontal stress gradient of 42.9 ±  28.5 MPa·km -1 . Based on the predicted stress tensor, we estimate the maximum pressure required to enhance the rock permeability and discuss the potential EGS development options for the Acoculco geothermal area.